PENGARUH MEDIA ANIMASI TERHADAP PEMAHAMAN PENGELOLAAN SAMPAH PADA MATA PELAJARAN IPAS DI SD DAARUL QURAN INTERNASIONAL - Fathuri, Amir; Miftachudin; Muttaqin, Muhammad Fauzan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the influence of animated video media in understanding waste management in science and science subjects to improve elementary school students' learning outcomes. The type of research used was Quasi Experiment with Nonequivalent Control Group Design, namely research conducted in two classes, namely the experimental class and the control class. This research was conducted in class V of Daarul Quran International Elementary School, Tangerang city. Data collection techniques using tests and observations. Data validation through content validity, instrument testing, reliability testing. Data analysis uses inferential statistical techniques through normality tests, homogeneity tests, and T tests. Based on the research results, the average learning outcomes test score before being given treatment (pretest) in the experimental class is 45.38, while the average learning outcomes test score afterwards. given treatment (posttest) was 81.54. And the results of the hypothesis test show a sig (2-tailed) result of 0.49 where 0.49 > 0.05 means Ho is rejected and Ha is accepted. This means that there is a difference in the use of animated video media in understanding waste management material in science and science subjects in class V of Daarul Quran International Elementary School, Tangerang city between before being given treatment (pretest) and after being given treatment (posttest). So, there is an influence of animated video media in understanding waste management material in the science and sciences subject to improve the learning outcomes of fifth grade elementary school students at Daarul Quran International Elementary School, Tangerang city for the 2023/2024 academic year.